A Comparison of Oral and Intravenous Glutamine Therapy Effects On Mucositis Development in Acute Leukemic Patients After High Dose Chemotherapy Supplementation - Demir, A. Dilara; Kiki, Ilhami (Archives of Clinical and Biomedical Research, 2017)
Aim: We compared the oral and intravenous glutamine therapy effects on mucositis development in acute leukemia patients after high dose chemotherapy supplementation. This research was applied in high dose chemotherapy patients in order to determine the effects of parenteral glutamine support on mucositis development. The results of oral and parenteral glutamine therapy are compared and analyzed for variations in mucositis formation. Materials and Methods: The present study includes the results of glutamine therapy performed on two patient groups. A total of 70 individuals (33 female and 37 male) were included in the study. Out of these patients, 35 were given oral glutamine whereas the remaining 35 were given glutamine via an intravenous route following chemotherapy. Patients were between 16 and 71 years of age. IV-therapy and oral therapy patients were selected as first and second groups, respectively. The same amount of Lalanyl Glutamine solution was given to both groups in equal time intervals. Mucositis grading was performed according to the criteria of the American Academy of Pediatric Dentistry and staging was carried out according to oral mucositis index. Results: When records of both groups were analyzed seperately, mild to moderate mucositis was determined in 85.7% (30 of 35) of the patients whereas severe mucositis was observed in 14.3% (5 of 35) patients who received oral glutamine support. On the other hand, mild- to moderate mucositis developed in all 35 patients (100%) who received intravenous glutamine support, but no severe mucositis developed in those patients. Conclusion: The result of this work can be summarized as; neither oral nor parenteral glutamine therapy prevents mucosite development, but parenteral glutamine therapy has a preventative effect on the development of severe mucositis.